I see you everywhere - Glass, Julia (New York : Pantheon Books, 2008)
Louisa Jardine is the older one, the conscientious sister who is a good student, and yearns for a good marriage, a career and a family. Clem Jardine is the younger sister -- the uncontainable rebel, daring and irresistible to men, and a constant source of frustration to her more reliable sister. Alternating between the sisters voices, I See You Everywhere unfolds across a 25-year span, from 1980 to 2005, beginning when Louisa and Clem are in their early twenties. A tale of jealousy and anger, affection and devotion.
Keywords: Sisters -- Fiction; Domestic fiction